A transformation grammar-based methodology for housing rehabilitation: meeting contemporary functional and ICT requirements - Eloy, Sara (2014)
This research starts from the premise that the future of the real estate market in Portugal will require the rehabilitation of existing residential areas in order to respond to new life-styles and dwelling requirements that have emerged in an era in which information plays a structuring role in society. The goal of this research is the definition of design guidelines and a rehabilitation methodology to support architects involved in the process of adapting existing dwellings, allowing them to balance sustainability requirements and economic feasibility with new dwelling trends such as the incorporation and updating of Information Communication and Automation Technologies and the need to solve emerging conflicts affecting the use of space prompted by the introduction of new functions associated with such technologies. In addition to defining a general methodology applicable to all the building types, the study focuses on a specific type, called “rabo-de-bacalhau” (“cod-tail”), built in Lisbon between 1945 and 1965 for which a specifc methodology has been generated. Both shape grammar and space syntax were used as part of the rehabilitation methodology as tools to identify and encode the principles and rules behind the adaptation of existing houses to new requirements.